Carcinoid Syndrome-Induced Scleroderma-Like Disease - Karen Koch; Wayne Grayson (MDPI AG, 2019)
Scleroderma is a rare complication of carcinoid syndrome and is usually encountered in the setting of a metastatic primary neuroendocrine tumour of the distal ileum. Associated endocardial fibrosis is a frequent finding and the condition carries a poor prognosis. We report a case of scleroderma occurring in a 72-year-old female with metastatic neuroendocrine carcinoma and associated pericardial fibrosis. The use of an alternative nomenclature such as "scleroderma-like" or "sclerodermoid" disease is proposed in order to emphasise its distinction from true idiopathic scleroderma, despite the histopathological similarities on skin biopsy.